Experience of Knowledge Sharing Among the Teachers in Higher Education - Upadhyay, Giri Raj (AMC Journal, 2023)
Knowledge sharing experience among teachers in higher education practice is important now a days. This study aims at exploring the experiences of the knowledge-sharing process among teachers in a higher education institution. It highlights teachers’ professional experience professionally in knowledge sharing. Social-constructivist perspectives and phenomenological study frameworks are used. Data was collected by conducting in-depth interviews with two people from a college under Tribhuvan University, an institution of higher education. Data were analyzed by coding, creating themes, showing interrelationships, and reasoning. Results show that institutional culture and politics, teacher rewards, beliefs, status, and professional ethics and standards influence decisions to share or withhold knowledge with some teacher colleagues. The outcomes focus on professional conditions, political influences, and incentives all have a significant impact on knowledge sharing, with institutionalized processes and hierarchies affecting the willingness of educators to share expertise. Trust and ethical considerations are also important, with trust and perceptions of ethical standards affecting active involvement and cooperation. This study recommends that knowledge sharing is a productive topic to carry out research in the future.